2006
DOI: 10.1111/j.1365-2036.2006.02907.x
|View full text |Cite
|
Sign up to set email alerts
|

Treatment with botulinum toxin of octo‐nonagerians with oesophageal achalasia: a two‐year follow‐up study

Abstract: SUMMARY BackgroundTreatment of oesophageal achalasia with intrasphincteric injections of botulinum toxin has proved to be a successful alternative treatment modality. However, little is known about its long-term effects in very old patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 31 publications
0
10
0
Order By: Relevance
“…A single injection of botulinum toxin has been shown to be effective in approximately 85% of patients with achalasia, but its effect diminishes over time (50% at 6 months and 30% at 1 year) [9,13,14], and universal symptomatic relapse occurs at 2 years [15].This treatment effect can be maximized by repeat injections [16], but its long-term effectiveness remains limited. The best results of botulinum toxin have been achieved in older patients [17] who tend to have higher lower esophageal pressures than younger patients [18], patients with vigorous achalasia, and patients whose LES pressures do not exceed C50% of the upper limit of normal [14,19]. In contrast, a lack of an initial symptomatic response and residual LES pressure C18 mmHg after botulinum toxin indicates patients unlikely to respond to further treatment with botulinum toxin [20].…”
Section: Botulinum Toxin Injectionsmentioning
confidence: 83%
See 1 more Smart Citation
“…A single injection of botulinum toxin has been shown to be effective in approximately 85% of patients with achalasia, but its effect diminishes over time (50% at 6 months and 30% at 1 year) [9,13,14], and universal symptomatic relapse occurs at 2 years [15].This treatment effect can be maximized by repeat injections [16], but its long-term effectiveness remains limited. The best results of botulinum toxin have been achieved in older patients [17] who tend to have higher lower esophageal pressures than younger patients [18], patients with vigorous achalasia, and patients whose LES pressures do not exceed C50% of the upper limit of normal [14,19]. In contrast, a lack of an initial symptomatic response and residual LES pressure C18 mmHg after botulinum toxin indicates patients unlikely to respond to further treatment with botulinum toxin [20].…”
Section: Botulinum Toxin Injectionsmentioning
confidence: 83%
“…Other predictors of treatment failure with balloon dilation include the presence of pulmonary symptoms and failed response to the first or second initial dilations [29,34,35]. Some authors have recommended the routine use of manometry before and after intervention, because high initial LES pressures (e.g., [15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30] or a reduction of LES pressure \ 50% after the first dilation have been found to be predictors of poor outcomes [29,35].…”
Section: Dilatationmentioning
confidence: 99%
“…Moreover, Bassotti et al [31] used a different modality of administration and reported an 80% success rate at 12 months in patients receiving two injections of botulinum toxin within a 4-week interval, thus arousing new interest in this therapy. It is essential to carry out more high-quality studies to identify the efficacy of repeated botulinum toxin injection treatment and botulinum toxin injection combined with other treatment methods.…”
Section: Discussionmentioning
confidence: 97%
“…However, Bassotti et al [56] using a different BoTx regimen, consisting of two injections within a 4-wk period, reported a success rate 80% at 12 mo. These findings may encourage new interest in this therapy.…”
Section: Discussionmentioning
confidence: 99%